Permafrost Thaw Accelerates Old Soil Carbon Release, Outpacing New Plant Inputs During a 13‐Year Tundra Warming Experiment - Emma Lathrop; Craig See; Xanthe Walker; Grant Falvo; Zev Axler; Christopher Ebert; Stephanie Kadej; Allison Kelley; Justin Ledman; Sophie Opfergelt; Heidi Rodenhizer; Edward A. G. Schuur (Global Change Biology, 2025)
Massive stores of ancient soil organic carbon (SOC) in permafrost can decompose with Arctic warming and accelerate global climate change. Declining SOC stocks are central to the permafrost carbon feedback, but direct measures of SOC loss are extremely rare due to methodological challenges related to subsidence in the Arctic. To fully capture changing SOC dynamics during thaw, we directly measured SOC stock and bulk soil radiocarbon ( 14 C) changes, while accounting for subsidence, during 13 years of permafrost thaw in a warming experiment in Interior Alaska. We found significant declines in SOC stocks: 14% (± 6%) in ambient plots that experienced regional warming and 23% (± 5%) in snow fence warmed plots, entirely in deep, mineral soil layers. Losses were largely driven by winter soil warming but were mediated by changing soil moisture and vegetation conditions. Plots with low shrub biomass had greater SOC losses, suggesting that vegetation community composition may play an important role in SOC storage. Surface soil 14 C measurements suggest that carbon inputs were three times greater in warming plots compared to ambient plots, but that decomposition increased proportionally leading to no detectable change in surface organic layers. We observed significant SOC losses of 5.2–8.1 kg C m −2 from deeper soil layers where carbon was sequestered ~2400 to ~4500 years ago. Our findings indicate that warmer soils in the winter will accelerate SOC losses, but that increasing density of shrub species through shrub expansion could help to mitigate SOC losses in deep soils. The significant loss of SOC from deep, mineral soils observed over just 13 years of ambient and experimental permafrost thaw highlights the vulnerability of this old C pool as it enters the active global carbon cycle.

Abrupt permafrost thaw drives spatially heterogeneous soil moisture and carbon dioxide fluxes in upland tundra - Heidi Rodenhizer; Susan M. Natali; Marguerite Mauritz; Meghan A. Taylor; Gerardo Celis; Stephanie Kadej; Allison K. Kelley; Emma R. Lathrop; Justin Ledman; Elaine F. Pegoraro; Verity G. Salmon; Christina Schädel; et al. (Global Change Biology, 2023)
Permafrost thaw causes the seasonally thawed active layer to deepen, causing the Arctic to shift toward carbon release as soil organic matter becomes susceptible to decomposition. Ground subsidence initiated by ice loss can cause these soils to collapse abruptly, rapidly shifting soil moisture as microtopography changes and also accelerating carbon and nutrient mobilization. The uncertainty of soil moisture trajectories during thaw makes it difficult to predict the role of abrupt thaw in suppressing or exacerbating carbon losses. In this study, we investigated the role of shifting soil moisture conditions on carbon dioxide fluxes during a 13‐year permafrost warming experiment that exhibited abrupt thaw. Warming deepened the active layer differentially across treatments, leading to variable rates of subsidence and formation of thermokarst depressions. In turn, differential subsidence caused a gradient of moisture conditions, with some plots becoming consistently inundated with water within thermokarst depressions and others exhibiting generally dry, but more variable soil moisture conditions outside of thermokarst depressions. Experimentally induced permafrost thaw initially drove increasing rates of growing season gross primary productivity (GPP), ecosystem respiration ( R eco ), and net ecosystem exchange (NEE) (higher carbon uptake), but the formation of thermokarst depressions began to reverse this trend with a high level of spatial heterogeneity. Plots that subsided at the slowest rate stayed relatively dry and supported higher CO 2 fluxes throughout the 13‐year experiment, while plots that subsided very rapidly into the center of a thermokarst feature became consistently wet and experienced a rapid decline in growing season GPP, R eco , and NEE (lower carbon uptake or carbon release). These findings indicate that Earth system models, which do not simulate subsidence and often predict drier active layer conditions, likely overestimate net growing season carbon uptake in abruptly thawing landscapes.